Information Management in Incentive Problems - Lewis, Tracy R.; Sappington, David E. M. (Journal of Political Economy, 1997)
We extend the standard procurement model to examine how an agent is optimally induced to acquire valuable planning information before he choose an unobservable level of cost‐reducing effort. Concerns about information acquisition cause important changes in standard incentive contracts. Reward structures with extreme financial payoffs arise, and super‐high‐powered contracts are coupled with contracts that entail pronounced cost sharing. However, if the principal can assign the planning and production tasks to two different agents, then all contracting distortions disappear and, except for forgone economies of scope, the principal achieves her most preferred outcome.